2022
DOI: 10.1007/s00405-022-07253-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cochlear implantation on cognitive decline and quality of life in younger and older adults with severe-to-profound hearing loss

Abstract: Purpose (a) To measure the change in cognition, the improvement of speech perception, and the subjective benefit in people under and over 60 years following cochlear implantation. (b) To assess the relationship between cognition, demographic, audiometric, and subjective outcomes in both age groups. Methods 28 cochlear implant (CI) users were assigned to the < 60y group and 35 to the ≥ 60y group. Cognition was measured using the Repeatable Battery for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
1
5
1
1
Order By: Relevance
“…In 2017, the Lancet Commission of Dementia Prevention, Intervention, and Care reported a new model of dementia risk [ 1 , 2 ] stating that hearing impairment may account for 8% of dementia cases [ 3 ]. Indeed, hearing loss (HL) is considered the biggest controllable risk factor for dementia, potentially reducing its risk by 9% [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2017, the Lancet Commission of Dementia Prevention, Intervention, and Care reported a new model of dementia risk [ 1 , 2 ] stating that hearing impairment may account for 8% of dementia cases [ 3 ]. Indeed, hearing loss (HL) is considered the biggest controllable risk factor for dementia, potentially reducing its risk by 9% [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last seven years, several studies have investigated this topic, e.g., refs. [ 3 , 14 , 16 , 18 , 19 , 20 , 21 , 22 , 23 ]. These studies found controversial results: some of them indicated postoperative cognitive improvement, e.g., ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Situaciones excepcionales como la pandemia de COVID-19 han venido a entorpecer aún más la comunicación para las personas con pérdida auditiva debido a que las mascarillas impiden la lectura de labios, como han denunciado en España FIAPAS (Confederación Española de Familias Una solución eficaz para tratar la presbiacusia y reducir la fragilidad cognitiva es el uso de audífonos, que aumentan la intensidad de los sonidos que recibimos, o de implantes cocleares, que estimulan directamente a las terminaciones nerviosas en el oído interno. Las personas que utilizan estos dispositivos reducen considerablemente la pérdida de memoria auditiva, mejoran la interacción social y, en definitiva, disminuyen el deterioro cognitivo asociado a la edad (Calvino et al, 2022;Maharani et al, 2018).…”
Section: Introductionunclassified